Analisis Peran Kampanye Di Media Sosial Dalam Membentuk Persepsi Publik Tentang Pemilu Presiden 2024 - Nur Maria Lubis; Efendi, Erwan (Asosiasi Ide Bahasa Kepri, 2024)
Social media is a powerful platform for accessing information, sharing information, and influencing public opinion. Therefore, it is very important to understand how social media is used in political campaigns to influence public perception. The aim of this research is to determine the influence of social media on public perception, with a focus on the use of social media in political campaigns. This research uses a qualitative descriptive approach to analyze several political campaigns in which social media is the main communication tool. Data is collected through observation, interviews and decision studies. Based on this research, it can be concluded that the use of social media in political campaigns has a significant impact on political behavior and public awareness. Social media provides people with the opportunity to exchange opinions through discussions, comments and various campaign-related content that influence public opinion.